What’s in a Hut Tomb? Cemetery Mapping in Eastern Oman 2017-2023, Preliminary Report - Yule, Paul A.; Gaudiello, Michela; Blum, Stephan; Hammes, Jannick (Zeitschrift für Orient-Archäologie, 2026)
The following evaluates 778 tombs surveyed, 295 from the BEW salvage excavations in the Bāṭina, and 361 excavated from Samad/al‑Muyasser. We entered long‑known and also new sites into an open-source database known as ‘Ent’ – an ongoing effort. Two issues arise for the hut tomb chronology: to determine a more specific nomenclature of the tomb shapes and to date by means of contexted finds. To the extent possible, we disambiguate hut tombs from other burial structures. Specific stone structures previously identified as ‘cairns’ can be more closely typologised. Dating tombs more finely than to the Early Iron Age or late pre‑Islamic period is rarely realistic. Excavated, poorly preserved tombs shed little light on the dating of well‑preserved hut tombs.
Keywords: Achéologie -- Oman